STRATEGIES FOR IMPROVING EMPLOYEE PERFORMANCE THROUGH PROGRAMS TO STRENGTHEN SELF-EFFICACY, SUPERVISION, AND WORK MOTIVATION - Handy Ariestino; Widodo Sunaryo; Herdiyana Herdiyana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The performance of Taxpayers (AR) at the Primary Tax Office (KPP Pratama) in the Bogor area still shows achievements that are not yet optimal. This condition necessitates a study to identify the factors influencing employee performance. This study aims to analyze the influence of self-efficacy and supervision on the performance of Account Representatives, both directly and thru work motivation as a mediating variable. This research uses a quantitative approach with a population consisting of all Account Representatives from the KPP Pratama in the Bogor Region, totaling 133 employees. The sample was determined using a census technique and involved 100 respondents. Data was collected thru questionnaires that had been tested for validity and reliability, and then analyzed using path analysis with SmartPLS version 4. The research results indicate that self-efficacy, supervision, and work motivation have a positive and significant effect on employee performance. Self-efficacy and supervision were also found to have a positive and significant impact on work motivation, which subsequently mediates the influence of these two variables on the performance of Account Representatives. These findings confirm that strengthening self-efficacy, supervision, and work motivation are important strategies for improving the performance of Account Representatives.